Varietal Evaluation of Potato Microtuber and Plantlet in Seed Tuber Production - Md. Sadek Hossain; M. Mofazzal Hossain; M. Moynul Haque; Md. Mahabubul Haque; Md. Dulal Sarkar (International Journal of Agronomy)
Diamant, Asterix, and Granola varieties differed significantly in foliage coverage, plant height, and yield. They produced lower graded minituber (67.62%, 78.16% ha−1, and 66.27% of Asterix, Granola, and Diamant varieties, resp.) as per seed rule of the National Seed Board of Bangladesh, while foliage coverage (74.38%) was the maximum in Diamant. Microtuber in field condition showed the maximum survivability, plant height, foliage coverage, number of stems plant−1, and SPAD value as well as yield of minituber compared to plantlet. On the contrary, microtuber derived plants of the three varieties gave the maximum yield (20.49 t ha−1, 19.12 t/ha−1, and 19.98 t ha−1 of Asterix, Granola, and Diamant varieties, resp.) and it was the minimum in plants of plantlets derived from all varieties (9.50 t ha−1, 7.88 t ha−1, and 9.70 t ha−1 of Asterix, Granola, and Diamant varieties, resp.). Microtuber derived plants produced a minimum percentage of <28 mm size of minituber compared to plantlet derived plants in case of all varieties.